Enantioselective Synthesis of Chiral Isotopomers of 1‐Alkanols by a ZACA–Cu‐Catalyzed Cross‐Coupling Protocol1. Issue 49 (28th October 2014) - Xu, Shiqing; Oda, Akimichi; Negishi, Ei‐ichi
Abstract Chiral compounds arising from the replacement of hydrogen atoms by deuterium are very important in organic chemistry and biochemistry. Some of these chiral compounds have a non‐measurable specific rotation, owing to very small differences between the isotopomeric groups, and exhibit cryptochirality. This particular class of compounds is difficult to synthesize and characterize. Herein, we present a catalytic and highly enantioselective conversion of terminal alkenes to various β and more remote chiral isotopomers of 1‐alkanols, with ≥99 % enantiomeric excess (ee), by the Zr‐catalyzed asymmetric carboalumination of alkenes (ZACA) and Cu‐catalyzed cross‐coupling reactions. ZACA‐in situ iodinolysis of allyl alcohol and ZACA‐in situ oxidation of TBS‐protected ω‐alkene‐1‐ols protocols were applied to the synthesis of both (R)‐ and (S)‐difunctional intermediates with 80–90 % ee. These intermediates were readily purified to provide enantiomerically pure (≥99 % ee) compounds by lipase‐catalyzed acetylation. These functionally rich intermediates serve as very useful synthons for the construction of various chiral isotopomers of 1‐alkanols in excellent enantiomeric purity (≥99 % ee) by introducing deuterium‐labeled groups by Cu‐catalyzed cross‐coupling reactions without epimerization.